2003
DOI: 10.1002/cyto.a.10092
|View full text |Cite
|
Sign up to set email alerts
|

Cell proximity is a prerequisite for the proliferative response of bystander cells co‐cultured with cells irradiated with γ‐rays

Abstract: Background In a recent study, we showed that unirradiated cells, when they are in the presence of cells irradiated with γ‐rays, are characterized by enhanced cell growth (Cytometry 2003;54A:1–7). However, the mechanisms and factors involved in the proliferative response of bystander cells are largely unknown. The aim of the current work was to investigate the possible role of spatial proximity of cells, including gap junctional intercellular communication (GJIC), in transmitting proliferation signals from cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 30 publications
4
55
1
Order By: Relevance
“…The range of the bystander signal in tissue, up to 1 mm, corresponds to Ϸ50-75 cell diameters. This surprisingly long range implies either that directly damaged cells produce long-range, diffusible bystander signals, perhaps through autocrine͞paracrine mechanisms (34)(35)(36)(37), or that a cell relay system is active, in which cells signal only their immediate neighbors (juxtacrine signaling), the signal being relayed by spatially intermediate, unirradiated bystander cells (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The range of the bystander signal in tissue, up to 1 mm, corresponds to Ϸ50-75 cell diameters. This surprisingly long range implies either that directly damaged cells produce long-range, diffusible bystander signals, perhaps through autocrine͞paracrine mechanisms (34)(35)(36)(37), or that a cell relay system is active, in which cells signal only their immediate neighbors (juxtacrine signaling), the signal being relayed by spatially intermediate, unirradiated bystander cells (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, several cytokines can be induced by ROS and NO/NOS (Ayache et al, 2002;Hsu and Wen, 2002;Kosmidou et al, 2002;Hwang et al, 2004;Ryan et al, 2004) providing a possible link between different factors potentially involved in bystander signalling. End points used for the study of bystander effects in vitro have included micronuclei formation (Azzam et al, 2002;Kashino et al, 2004;Shao et al, 2004), gene mutations and genomic instability (Zhou et al, 2000), gene expression changes (Azzam et al, 2002;Yang et al, 2005), transformation (Sawant et al, 2001), proliferation (Gerashchenko and Howell, 2003), cell survival, apoptosis (Belyakov et al, 2002;Lyng et al, 2002), cell cycle arrest (Azzam et al, 2000) and most recently the induction of gH2AX foci in bystander cells (Hu et al, 2005;Sokolov et al, 2005;Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Azzam et al (7) used these cells to provide direct evidence for the participation of GJIC in the transmission of damage signals from ␣-particles irradiated to bystander cells. Using WB-F344 cells, radiation-induced bystander effects have also been observed by Gerashchenko and Howell (8,9). It was found that WB-F344 cells that were irradiated with ␥-rays stimulated proliferation in unirradiated bystander cells (8).…”
mentioning
confidence: 55%
“…It was found that WB-F344 cells that were irradiated with ␥-rays stimulated proliferation in unirradiated bystander cells (8). Close proximity between the irradiated and bystander cells was a prerequisite for the proliferative response of the bystanders (9).…”
mentioning
confidence: 99%